2008
DOI: 10.1089/lap.2008.0191
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Approach to Ovarian Mass in Children and Adolescents: Already a Standard in Therapy

Abstract: Treatment is indicated if the diagnosis is in question, the cyst persists, in the case of ovarian torsion,or if the patient is symptomatic. Laparoscopy is becoming the favored approach by most pediatric surgeons for the treatment of ovarian cysts. All surgical procedures for ovarian cysts should spare functional ovary as much as is technically possible. Simple cysts can be fenestrated, but complex or functional cysts should be excised, with the preservation of the remaining ovary by careful dissection. The lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…Performance of laparoscopy as minimally invasive surgery can be useful for both diagnosis and treatment. Mayer and colleagues previously suggested that laparoscopy is associated with satisfactory outcomes and few complications (Mayer et al, 2009). We also generally preferred laparoscopy for the surgical treatment and performed cystectomy in the majority of patients.…”
Section: Figure 1 Roc Curve Analysis For Plr In Prediction Of Adolesmentioning
confidence: 99%
“…Performance of laparoscopy as minimally invasive surgery can be useful for both diagnosis and treatment. Mayer and colleagues previously suggested that laparoscopy is associated with satisfactory outcomes and few complications (Mayer et al, 2009). We also generally preferred laparoscopy for the surgical treatment and performed cystectomy in the majority of patients.…”
Section: Figure 1 Roc Curve Analysis For Plr In Prediction Of Adolesmentioning
confidence: 99%
“…In contrast, laparoscopic surgery has been widely recognized as the gold standard in the management of adnexal masses for which malignancy can be excluded preoperatively (Mayer et al, 2009;Seckin et al, 2011). However, even when strict criteria are used to limit the use of laparoscopic surgery to those patients whose masses are most likely to be benign, some patients who undergo laparoscopic surgery are intraoperatively or post-operatively determined to have malignant tumors (Muzii et al, 2005), a scenario known as unexpected ovarian malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, laparoscopic surgery has been accepted as the gold standard in the management of adnexal masses in gynecologic surgery and its advantages have been well documented in large adult series. 7 Also, there has been a notable shift from open surgery to laparoscopic approach in young females. 8 Minimally invasive surgery in this age group is especially important for future fertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are small series describing the efficacy and safety of laparoscopy for ovarian lesions in the adolescent and young adult population. 1e3, 7 The present study tried to investigate the laparoscopic management of ovarian masses in adolescents and young adults and review our experience about this subject.…”
Section: Introductionmentioning
confidence: 99%